2006
DOI: 10.1039/b507209n
|View full text |Cite
|
Sign up to set email alerts
|

Advances in cycloaddition polymerizations

Abstract: Cycloaddition reactions have been employed in polymer synthesis since the mid-nineteen sixties. This critical review will highlight recent notable advances in this field. For example, [2 + 2] cycloaddition reactions have been utilized in numerous polymerizations to enable the construction of strained polymer systems such as poly(2-azetidinone)s that can, in turn, afford polyfunctional beta-amino acid derived polymers. Polymers have also been synthesized successfully via (3 + 2) cycloaddition methods utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 152 publications
(119 reference statements)
0
92
0
Order By: Relevance
“…[5] After the independent discovery of the Cu(I) catalysis by Meldal and coworkers [6] and Sharpless and coworkers, [7] click chemistry has found entry to a manifold of applications in polymer science and meanwhile comprehensive review articles can be found in the literature. [8][9][10] Mostly, it was not only employed for polymer analogous side group [11,12] and end group modification of macromolecules [13,14] but also for the construction of hyperbranched materials [15,16] or linear polymers. [17] Not long after the introduction of click chemistry first attempts were undertaken to apply its advantages to functionalize surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5] After the independent discovery of the Cu(I) catalysis by Meldal and coworkers [6] and Sharpless and coworkers, [7] click chemistry has found entry to a manifold of applications in polymer science and meanwhile comprehensive review articles can be found in the literature. [8][9][10] Mostly, it was not only employed for polymer analogous side group [11,12] and end group modification of macromolecules [13,14] but also for the construction of hyperbranched materials [15,16] or linear polymers. [17] Not long after the introduction of click chemistry first attempts were undertaken to apply its advantages to functionalize surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…1,3-Dipolar cycloadditions found broad application in materials science and their popularity is highlighted in several remarkable reviews. 11,12 Nevertheless, a series of different reactive polymers had already been described in the past. 13 The chemistry of activated esters in polymer synthesis, however, has been neglected in recent years because of the dominating popularity of 1,3-dipolar cycloadditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it can interact productively in several ways with biological molecules and can serve as a hydrolytically-stable replacement for the amide bond [24][25][26]. Compatibility of the CuAAC reaction with a broad range of functional groups and reaction conditions [27][28][29][30][31] has made it broadly useful across the chemical disciplines, and its applications include the synthesis of biologically active compounds, the preparation of conjugates to proteins and polynucleotides, the synthesis of dyes, the elaboration of known polymers and the synthesis of new ones, the creation of responsive materials, and the covalent attachment of desired structures to surfaces [5,[32][33][34][35][36].…”
Section: Azide-alkyne Cycloaddition: Basicsmentioning
confidence: 99%